Edwin Seligman's lectures on public finance, 1927/1928 - Samuels, Warren J. (Research in the history of economic thought and methodology, 2001)
Edwin R.A. Seligman was a leading specialist in public finance, as well as the history of economic thought. This volume publishes a set of student notes taken in his famous course in public finance at Columbia University. The lectures cover the history of public revenues, types of public revenues in general and of taxation in particular, public expenditures, public debt, and budget making.